G209 White cell counts post-routine immunisations: implications for the management of febrile infants without infective focus. (27th April 2016) - Prentice, S; Kamushagga, Z; Elliott, AM; Dockrell, HM; Cose, S
Abstract : Aims: Fever is the most common reason for presentation of children to medical professionals. Clinical algorithms are particularly stringent for the management of children with fever under the age of 3 months, due to increased risks of occult bacteraemia. 1 Febrile well-looking infants between 1–3 months who have a white cell count >15 × 10 9 /litre are recommended to have a full septic screen, including lumbar puncture and be admitted for parenteral antibiotics. However, infants receive primary immunisations in the first 3 months of life. These are well known to cause fever, but there is no information about corresponding changes to leucocytes following their administration. This study investigated white cell counts in the period shortly following routine immunisations in infants under 3 months of age. Methods: 240 healthy Ugandan infants had blood samples collected at a range of time points following receipt of routine immunisations. White cell counts and inflammatory markers were measured on each sample, and routine clinical assessment was performed. Results: Mean leucocytes were 15.5 × 10 9 /litre at one-day post-immunisations, significantly different from pre-immunisation values. This was primarily a neutrophilia, with mean post-immunisation neutrophils above the normal reference range for age. White cell parameters returned to baseline at two days. No participant received antibiotics when presenting febrile post-immunisations and all remained well at follow-up. Conclusions: Our data suggest that more than 50% of children <3 months old presenting with fever one-day post-immunisations would meet the current NICE criteria for full septic screen and admission for parenteral antibiotics. Given that these children remain well and white cells counts return to baseline by day two, we suggest that clinical algorithms be amended to include higher white cell count ranges for children one day post-immunisations, or have a provision for observation and repeat blood tests in 24 h, without antibiotics and lumbar puncture, depending on the clinical condition of the child. Reference: Davis, T. NICE guideline: feverish illness in children-assessment and initial management in children younger than 5 years. Archives of disease in childhood Education and practice edition 2013;98, 232–35, doi:10.1136/archdischild-2013-304792